A Narrative Inquiry on the Students’ Academic Writing Experience’s in Post Pandemic - Shabrina Juliandini; Heni Novita Sari (Universitas Muhammadiyah Enrekang, 2023)
This study examines the impact of post-pandemic on undergraduate students' academic writing experiences in 2022-2023. It seeks to shed light on the challenges that students face in their academic writing. Narrative research is employed to understand the participants' lived and imagined experiences and the meaning they make of their own experiences through storytelling. The post-pandemic learning environment has changed the way students approach academic writing, with many struggling to adapt to the new online learning format. Solutions and support from parents, study partners, and the community can help overcome these challenges and foster creativity in students.